A randomized clinical trial on the effects of exercise on muscle remodelling following bariatric surgery - Saulo Gil; John P. Kirwan; Igor H. Murai; Wagner S. Dantas; Carlos Alberto Abujabra Merege‐Filho; Sujoy Ghosh; Samuel K. Shinjo; Rosa M.R. Pereira; Walcy R. Teodoro; Sheylla M. Felau; Fabiana B. Benatti; Ana L. deSá‐Pinto; et al. (Wiley, 2021)
Abstract Background Muscle atrophy and strength loss are common adverse outcomes following bariatric surgery. This randomized, controlled trial investigated the effects of exercise training on bariatric surgery‐induced loss of muscle mass and function. Additionally, we investigated the effects of the intervention on molecular and histological mediators of muscle remodelling. Methods Eighty women with obesity were randomly assigned to a Roux‐en‐Y gastric bypass (RYGB: n = 40, age = 42 ± 8 years) or RYGB plus exercise training group (RYGB + ET: n = 40, age = 38 ± 7 years). Clinical and laboratory parameters were assessed at baseline, and 3 (POST3) and 9 months (POST9) after surgery. The 6 month, three‐times‐a‐week, exercise intervention (resistance plus aerobic exercise) was initiated 3 months post‐surgery (for RYGB + ET). A healthy, lean, age‐matched control group was recruited to provide reference values for selected variables. Results Surgery resulted in a similar (P = 0.66) reduction in lower‐limb muscle strength in RYGB and RYGB+ET (−26% vs. −31%), which was rescued to baseline values in RYGB + ET (P = 0.21 vs. baseline) but not in RYGB (P < 0.01 vs. baseline). Patients in RYGB+ET had greater absolute (214 vs. 120 kg, P < 0.01) and relative (2.4 vs. 1.4 kg/body mass, P < 0.01) muscle strength compared with RYGB alone at POST9. Exercise resulted in better performance in timed‐up‐and‐go (6.3 vs. 7.1 s, P = 0.05) and timed‐stand‐test (18 vs. 14 repetitions, P < 0.01) compared with RYGB. Fat‐free mass was lower (POST9‐PRE) after RYBG than RYGB + ET (total: −7.9 vs. −4.9 kg, P < 0.01; lower‐limb: −3.8 vs. −2.7 kg, P = 0.02). Surgery reduced Types I (~ − 21%; P = 0.99 between‐group comparison) and II fibre cross‐sectional areas (~ − 27%; P = 0.88 between‐group comparison), which were rescued to baseline values in RYGB+ET (P > 0.05 vs. baseline) but not RYGB (P > 0.01 vs. baseline). RYGB + ET showed greater Type I (5187 vs. 3898 μm2, P < 0.01) and Type II (5165 vs. 3565 μm2, P < 0.01) fCSA than RYGB at POST9. RYGB + ET also resulted in increased capillarization (P < 0.01) and satellite cell content (P < 0.01) than RYGB at POST9. Gene‐set normalized enrichment scores for the muscle transcriptome revealed that the ubiquitin‐mediated proteolysis pathway was suppressed in RYGB + ET at POST9 vs. PRE (NES: −1.7; P < 0.01), but not in RYGB. Atrogin‐1 gene expression was lower in RYGB + ET vs. RYGB at POST9 (0.18 vs. 0.71‐fold change, P < 0.01). From both genotypic and phenotypic perspectives, the muscle of exercised patients resembled that of healthy lean individuals. Conclusions This study provides compelling evidence-from gene to function-that strongly supports the incorporation of exercise into the recovery algorithm for bariatric patients so as to counteract the post‐surgical loss of muscle mass and function.